Illicit Drug Use among Commercial 'Boda Boda' Motorcyclists in Uganda. (24th August 2022) - Kwagala, Betty; Ndugga, Patricia; Nankinga, Olivia; Wamala, Twaibu; Zarugaba, Ignatius Tinka; Richard, Sendi; Misinde, Cyprian; Nansubuga, Elizabeth; Katende, Dan; Mbonye, Martin
Abstract: Background: Illicit drug use is a global public health problem with grave health and socio-economic consequences. Related intoxication has been associated with accidental injuries and fatalities. In Uganda, 67% of road traffic accidents are attributed to motorcyclists. Methods: This study assessed the prevalence and determinants of illicit drug use among commercial motorcyclists in Uganda, using a cross-sectional survey research design. We interviewed 785 commercial motorcyclists in the divisions of Nakawa, Rubaga, Makindye, and Kawempe of Kampala district. We used an on-spot saliva drug test kit to screen and detect the presence of illicit drugs. Data were analyzed using frequency distributions, cross tabulations and multi variable logistic regression. Results: Findings show that 11% of the cyclists used illicit drugs. The use of illicit drugs was associated with division of operation, religiosity, and whether a cyclist resided with a family. The odds of use of illicit drugs were higher among cyclists from Nakawa division compared to cyclists from Kawempe. Cyclists who went to places of worship on a weekly basis compared to those who were less frequent, and cyclists who lived with their families compared to those who did not, had reduced odds of use of illicit drugs. There are variations in the distribution of cyclists that use illicit drugs in Kampala. Religious commitment and residence with families had a mitigating influence on illicit drug use among commercial cyclists. Conclusion: Illicit drug use prevention, treatment, and harm reduction programs among cyclists should collaborate with faith-based organizations and other key stakeholders, and promote stable family relations.